Anemia: A Diagnostic Malady in Management of Dengue Patients - Afsar, Nabila; Nagma, Sabahat Zamani; Afroze, Idrees Akhtar (Annals of Pathology and Laboratory Medicine, 2019)
Background: With the high prevalence of anemia and increasing incidence of dengue in developing countries like India, diagnosis of anemia in dengue patients needs to be stressed. There is higher hemoglobin and hematocrit as a result of plasma leakage in dengue, hence diagnosis and treatment of anemia may be missed. Methods: Hospital based retrospective study was done on 138 patients diagnosed with Dengue fever during the year 2017, in a tertiary care teaching hospital in Hyderabad. The CBC data was retrieved and statistical analysis was performed. Result: 60% of patients >5 yrs of age showed low Hb however hypochromia on smear was noted in 93.3% of cases. In patients aged 5-11yrs and 12-14 yrs, 31.4% and 14.3% respectively had low Hb, but hypochromia was noted in 48.6% and 57.1% .In non pregnant females, 68.4% showed low Hb while 55.3% cases showed Hypochromia. In males,25% of cases showed low Hb whereas 13.9% showed Hypochromia. An analysis of 36 in patents with >3 reports was done to demonstrate the variation in Hb,MCV and MCH during course of admission. There was wide variability in Hb concentration of same patient on CV above 1% in 91.7% of the cases. MCV and MCH had CV more than 1.1% and 0.5% in 25% and 69.4% of the cases respectively. Conclusion: MCV is a stable parameter which can be used to assess the morphological status of the RBC even in a background of heamoconcentration. Complication of volume overload needs to be avoided in an anemic patient suffering from dengue .The importance of inclusion of red cell indices especially MCV in CBC reports is stressed.